The Effect of Work Motivation and Self-Confidence on Employee Performance at Bank Indonesia Cirebon - Aurellya, Nanda Hakimah; Nurdiana , Editya (Cv. Syntax Corporation Indonesia, 2026)
Employee performance in the banking sector is influenced by various psychological factors, particularly within the context of institutional transformation and digitalization. This study aims to analyze the effect of work motivation and self-confidence on employee performance at Bank Indonesia Cirebon. A quantitative approach using an associative research design was employed, involving 60 employees as respondents selected through saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results showed that work motivation has a positive and significant effect on employee performance (β = 0.550; t = 5.069; p < 0.05), while self-confidence also has a positive and significant effect (β = 0.430; t = 3.978; p < 0.05). The R² value of 0.946 indicates that both variables simultaneously explain 94.6% of the variance in employee performance. These findings confirm that work motivation and self-confidence are key determinants of employee performance in the banking sector. This study recommends that Bank Indonesia strengthen employee work motivation and self-confidence through structured training programs, coaching and mentoring systems, transparent performance-based reward mechanisms, and the creation of a work environment that supports autonomy and active participation.